Measurement of the CP-violating phase phi sJ/psi phi using the flavor-tagged decay Bs(0) -> J/psi phi in 8 fb(-1) of p(p)over-bar collisions - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Vesterinen, M.; et al. (Amer Physical Soc, 2012)
We report an updated measurement of the CP-violating phase, phi(J/psi phi)(s), and the decay-width difference for the two mass eigenstates, Delta Gamma(s), from the flavor-tagged decay B-s(0) -> J/psi phi. The data sample corresponds to an integrated luminosity of 8.0 fb(-1) accumulated with the D0 detector using p (p) over bar collisions at root s = 1.96 TeV produced at the Fermilab Tevatron collider. The 68% Bayesian credibility intervals, including systematic uncertainties, are Delta Gamma(s) = 0.163(-0.064)(+0.065) ps(-1) and phi(J/psi phi)(s) = -0.55(-0.36)(+0.38). The p-value for the Standard Model point is 29.8%.